Three-Phase Buck Type Pfc Rectifier for Electrical Vehicle Battery Charger - Demirkutlu, E.; İskender, İres; Iskender, I. (International Organization on 'Technical and Physical Problems of Engineering', 2019)
Three-phase AC/DC buck-type power factor correction (PFC) rectifier is presented in this paper. State of the art three-phase AC/DC rectifiers and improvements of the rectifier topologies are researched in this study. The SWISS Rectifier is implemented for Electrical Vehicle (EV) battery charger with 220 VLN-rmsS / 50 Hz three-phase input. The SWISS Rectifier for EV charger application is implemented by means of simulations. Depending upon the battery pack needs, 48 VDC output voltage is examined under both steady-state and dynamic load change conditions. © 2019, International Organization on 'Technical and Physical Problems of Engineering'. All rights reserved.
Three-phase buck type pfc rectifier for electrical vehicle battery charger
Keywords: Battery Charger; Buck Type Pfc; Electrical Vehicle; Harmonic; Pfc; Power Factor Correction; Swiss Rectifier